2021
DOI: 10.1128/spectrum.00678-21
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Cultured and Total Bacterial Community in the Wheat Rhizosphere Microbiome Using Culture-Dependent and Culture-Independent Approaches

Abstract: Bacteria colonizing the rhizosphere, a narrow zone of soil surrounding the root system, are known to have beneficial effects in improving the growth and stress tolerance of plants. However, most bacteria in natural environments, especially those in rhizosphere soils, are recalcitrant to cultivation using traditional techniques, and thus their roles in soil health and plant growth remain unexplored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 55 publications
0
14
0
1
Order By: Relevance
“…In this way, until recently, it has been believed that culturing only offers a biased and useless description of the bacterial communities of a given environment (Ritz, 2007). However, an increasing number of works are demonstrating that culturing and metataxonomics are complementary to fully describe the microbial diversity in a given environment (Shade et al, 2012;Stefani et al, 2015;Youseif et al, 2021). In our study, phylogenetic comparison of the culture-dependent and -independent communities at OTU level showed that a total of 21 OTUs were detected only by culturing (Fig.…”
mentioning
confidence: 62%
“…In this way, until recently, it has been believed that culturing only offers a biased and useless description of the bacterial communities of a given environment (Ritz, 2007). However, an increasing number of works are demonstrating that culturing and metataxonomics are complementary to fully describe the microbial diversity in a given environment (Shade et al, 2012;Stefani et al, 2015;Youseif et al, 2021). In our study, phylogenetic comparison of the culture-dependent and -independent communities at OTU level showed that a total of 21 OTUs were detected only by culturing (Fig.…”
mentioning
confidence: 62%
“…One milliliter from the first sample diluent was added to 9 mL of 0.01% Tween 80 and vortexed to obtain the second sample diluent, and this process was repeated for the third sample diluent. One hundred microliters of the first, second, and third sample diluents was cultured on the bacterial isolation medium separately, and 100 μL of the first and second sample diluents was cultured on the fungal isolation medium separately ( 61 63 ).…”
Section: Methodsmentioning
confidence: 99%
“…Sequence reads were edited and assembled using DNA Baser assembly software ( www.DnaBaser.com ). Isolates were identified by comparing their 16S rRNA sequences with reference sequences available at Ezbiocloud ( https://www.ezbiocloud.net/ ) and GenBank ( www.ncbi.nlm.nih.gov ) databases as previously described in (Youseif et al 2021b ). The sequences were aligned using ClustalW matrix-based algorithm and were subjected to phylogenetic analyses using MEGA X software version 10 (Kumar et al 2018 ).…”
Section: Methodsmentioning
confidence: 99%